2010
DOI: 10.1111/j.1365-2222.2010.03620.x
|View full text |Cite
|
Sign up to set email alerts
|

Can childhood asthma be predicted at birth?

Abstract: Although at best 75% of children with a history of asthma could be predicted at birth, an intervention applied to our predicted high-risk children would be started more often in children without than with future disease. Parental allergic disease alone appears insufficient to identify high-risk populations in future studies of asthma and allergic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
(74 reference statements)
1
15
0
Order By: Relevance
“…Lundholm et al [105] demonstrated that increasing birth weight is a risk factor for AD, but not AR, clearly independent of gestational age, shared environmental and genetic factors. This indicates that fetal growth affects the immune system and points to early mechanisms in line with evidence from many birth cohort studies [79, 106–111]. Thomsen et al [112] confirmed the strong genetic component of asthma in children and adults, and that this may not extend to older adults.…”
Section: Epidemiology Of Allergic Diseasessupporting
confidence: 64%
“…Lundholm et al [105] demonstrated that increasing birth weight is a risk factor for AD, but not AR, clearly independent of gestational age, shared environmental and genetic factors. This indicates that fetal growth affects the immune system and points to early mechanisms in line with evidence from many birth cohort studies [79, 106–111]. Thomsen et al [112] confirmed the strong genetic component of asthma in children and adults, and that this may not extend to older adults.…”
Section: Epidemiology Of Allergic Diseasessupporting
confidence: 64%
“…However, these results might be biased by the administration of corticosteroids during the acute stage which might have caused suppression of cell activation, thereby reducing sCD14 levels in serum [49]. Multiple studies showed no association of sCD14 levels with asthma as measured in cord blood, serum or bronchoalveolar lavage fluid [23,50,51]. In one study no association of sCD14 levels in breast milk with wheeze was found [52].…”
Section: Resultsmentioning
confidence: 99%
“…The article in this issue of the journal by Lødrup Carlsen et al [9] has extended the investigation of this hypothesis further, by trying to predict who will develop asthma from information gathered at the time of birth. Using an extraordinary database on over 600 healthy babies, which includes lung function tests carried out in the first few days of life, they identify which factors predict who will develop asthma, allergic rhinitis and the absence of either condition by age 10.…”
mentioning
confidence: 99%
“…Although the resulting risk factor models developed by Lødrup Carlsen et al [9] were statistically significant for predicting asthma, rhinitis and ‘healthy’ (the absence of these diseases and negative skin prick tests) by age 10, the predictive value of the models were disappointing. The best model could predict 75% of asthma by age 10, but had poor specificity.…”
mentioning
confidence: 99%
See 1 more Smart Citation